An investigation on the improvement of construction expenditure forecasting - Ross, Andrew; Dalton, Katie; Sertyesilisik, Begum (Journal of Civil Engineering and Management, 2013)
This study aims to determine the accuracy of the cash flow models and to investigate if these models could be more accurate if they accounted for the potentially influential variables specific to individual construction projects. An analytical case study research strategy has been implemented in collecting data for the construction projects. The data collected has been tested against recognised models. Statistical analyses have been carried out on the data for the specified variables, culminating in the potential proposal of an improved model with respect to these identified variables. The results revealed that the independent variables (type of construction, procurement route and type of work) affect the cash flow forecast. The findings suggested that a model could be more accurate with the input of more job-specific variables and that Hudson’s DHSS model is best suited to a construction project procured traditionally. Adopting the ‘trial and error’ approach, Hudson’s DHSS model has been recognised as an accurate model that could be adapted slightly, through changing the parameter values. The clients and the contractors are the main beneficiaries approached for this study.